2004
DOI: 10.17159/2413-3108/2004/v16i2a182
|View full text |Cite
|
Sign up to set email alerts
|

Non-allergic activation of eosinophils after strenuous endurance exercise

Abstract: Objective. To determine the effect of prolonged endurance exercise on the serum concentrations of eosinophil cationic protein (ECP), immunoglobulin E (IgE) and upper respiratory tract symptoms (URTS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…Low effectiveness of intensity and duration of exercise in the prediction of the number of EOS may be because of more effects of EOS in allergic diseases and parasitic infections 46 . Moreover, it may show that these cells need more severe stress than the stress induced in this study 47 . Also, the high impact of intensity and duration of exercise on the prediction of WBC levels considering the effect of exercise on NEU, LYMPH, and MON and a large volume of them in leukocytes (NEU (about 60%), lymphocytes (about 30%), and MON (about 5.3%) 48 ), can be justifiable.…”
Section: Discussionmentioning
confidence: 70%
“…Low effectiveness of intensity and duration of exercise in the prediction of the number of EOS may be because of more effects of EOS in allergic diseases and parasitic infections 46 . Moreover, it may show that these cells need more severe stress than the stress induced in this study 47 . Also, the high impact of intensity and duration of exercise on the prediction of WBC levels considering the effect of exercise on NEU, LYMPH, and MON and a large volume of them in leukocytes (NEU (about 60%), lymphocytes (about 30%), and MON (about 5.3%) 48 ), can be justifiable.…”
Section: Discussionmentioning
confidence: 70%
“…Testosterone signaling action, via androgen receptors, demonstrates that neutrophils expressing androgen receptors are strongly impacted by hormonal changes and could explain the differentiated effects between sexes on the tissue regeneration mechanism in response to the training program. McKune et al (2004) observed an increase in the non-allergic activation of blood eosinophils immediately after the ultramarathon and it remained high until 72 hours later when compared to pre-exercise values in a sample composed of 11 experienced individuals (6 men and 5 women; 43.0 ± 9.8 years). Those authors suggested that strenuous exercise would cause bronchial hyperactivity that increases fluid loss and, subsequently, generates an osmotic change in the bronchial epithelium.…”
Section: Discussionmentioning
confidence: 83%
“…Os eosinófilos são reconhecidos como células pró-inflamatórios do trato respiratório, com considerável potencial de causar danos. O exercício aeróbico de resistência afeta tanto compartimentos sistêmicos quanto as vias respiratórias, aumentando a incidência de doenças infecciosas e alérgicas que provocam broncoconstrição e hiper-responsividade do epitélio respiratório (MCKUNE et al, 2004). Um efeito similar tem sido encontrado nos equinos atletas, principalmente os de corrida que são predispostos a desenvolver pleuropneumonia, porém, os macrófagos pulmonares dos cavalos parecem possuir interação mais complexa com o meio ambiente e com outras células do sistema imune que os dos humanos (RAIDAL et al, 2001).…”
Section: Kmunclassified
“…Outra possível explicação é que a resposta de fase aguda na musculatura lesionada ativa o sistema complemento (C3, C4 e C5) e esses fragmentos podem ativar os eosinófilos (DUFAUX et al, 1993). McKune et al (2004) (NIEMAN, 1997). O cortisol aumenta a liberação de neutrófilos da medula óssea na circulação e o aumento do débito cardíaco provoca turbilhonamento do sangue aumentando a mobilização de leucócitos de pools marginais como parede das veias (ROBSON et al, 2003).…”
Section: Kmunclassified